Is single parenthood increasingly an experience of less-educated mothers? A European comparison over five decades - Caroline Berghammer; Anna Matysiak; Torkild Hovde Lyngstad; Francesca Rinesi (Demographic Research)
BACKGROUND: A central question in family research is whether parents’ social disadvantages, such as being a single parent or having low education, are becoming more concentrated over time. OBJECTIVE: We contribute to this literature by examining long-term trends in the gap in single parenthood between more educated and less-educated mothers since the 1970s to around 2015, placing special emphasis on children’s age. METHODS: To this end, we rely on a unique compilation of censuses as well as labour force surveys from eight European countries representing different institutional and cultural contexts: Austria, France, Germany, Ireland, Italy, Norway, Poland, and the United Kingdom. The data were analysed using logistic regression models. RESULTS: Our results show that the gap in single motherhood between highly educated and less-educated women generally changed over the period: Single motherhood increased disproportionally among less-educated women. The gap widened most among mothers with young children (0 to 4 years) and somewhat less for mothers of children at age 5 to 9 years. For mothers with children aged 15+, the prevalence of single motherhood varied only moderately by the mothers’ level of education. CONTRIBUTION: These findings suggest that being a low-educated single mother and having responsibility for young children has become more tightly linked. This uncovers a double disadvantage in that low-educated single mothers who possess less resources also more frequently have younger-aged children in need of more time and other resources.